2021
DOI: 10.1109/tkde.2019.2961675
|View full text |Cite
|
Sign up to set email alerts
|

CED: Credible Early Detection of Social Media Rumors

Abstract: Rumors spread dramatically fast through online social media services, and people are exploring methods to detect rumors automatically. Existing methods typically learn semantic representations of all reposts to a rumor candidate for prediction. However, it is crucial to efficiently detect rumors as early as possible before they cause severe social disruption, which has not been well addressed by previous works. In this paper, we present a novel early rumor detection model, Credible Early Detection (CED). By re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 27 publications
0
60
0
Order By: Relevance
“…With regards to neural networks, RNNs are used by Ma et al [30] to learn hidden representations of posts, without the need of extracting hand-crafted features. The task of early detection of social media rumours is investigated by Song et al [38] proposing a model called Credible Early Detection. In contrast to existing methods, which typically need all reposts of a rumour for making the prediction, this work aims to make credible predictions soon after the initial suspicious post.…”
Section: Machine Learning Approachesmentioning
confidence: 99%
“…With regards to neural networks, RNNs are used by Ma et al [30] to learn hidden representations of posts, without the need of extracting hand-crafted features. The task of early detection of social media rumours is investigated by Song et al [38] proposing a model called Credible Early Detection. In contrast to existing methods, which typically need all reposts of a rumour for making the prediction, this work aims to make credible predictions soon after the initial suspicious post.…”
Section: Machine Learning Approachesmentioning
confidence: 99%
“…In many of the rumour detection strategies it is found that machine learning approaches requires frequent training of system using the labelled dataset in case of supervised strategy. Studies suggest that, instead of machine learning or ranking algorithmic approach, the pre-defined knowledge based rules sum-up with deep learning approaches (CNN/RNN) and Natural Language processing embedded with Semantic Ontology are found to be efficient when compared to earlier approaches [16] [8]. After keen observation of various datasets of different domain it is suggested that domain specific rumour words need to be used in a particular context for better precision rate.…”
Section: Problems Faced Due To Rumours In Snsmentioning
confidence: 99%
“…Detecting of short rumour tweets such as -Obama is a muslim guy‖, this does not require excessive learning for this authenticated books to be checked and a conclusion can be derived within seconds using a pre-defined rule based classifier [13]. In literature, most of the researchers had picked datasets of their own considering a particular scenario and few have taken from previously existed rumour datasets [3] [13] [16]. Many of the researchers had picked rumour dataset of microblogs from Twitter, Facebook, Weibo and Instagram to predict the category of rumours [1] [18].…”
Section: A Rumour Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the success of deep learning, many recent studies [8], [9] apply various neural networks for rumor detec-* is the corresponding author. tion.…”
Section: Introductionmentioning
confidence: 99%